The adoption and impact of an improved drought-tolerant, dual-purpose groundnut variety in Southern India - Teufel, Nils; Johnson, Nancy L.; Singh, D. (International Livestock Research Institute, 2011)
This paper looks at the adoption and impact of an improved groundnut cultivar in Anantapur district, Andhra Pradesh, India. Despite positive results in farmer-participatory varietal selection, adoption was extremely low despite promotional efforts of a local NGO. The few farmers who adopted the variety generated significant benefits. They earned higher profits per hectare and their agricultural asset portfolios (a measure of wealth) increased significantly more than those of non-adopters. This raises the question of why, if the variety is beneficial, adoption is so low. Some possible explanations and their implications for future varietal development and dissemination are discussed.